2016
DOI: 10.1051/alr/2016030
|View full text |Cite
|
Sign up to set email alerts
|

Technical mitigation measures for sharks and rays in fisheries for tuna and tuna-like species: turning possibility into reality

Abstract: Tuna fisheries have been identified as one of the major threats to populations of other marine vertebrates, including sea turtles, sharks, seabirds and marine mammals. The development of technical mitigation measures (MM) in fisheries is part of the code of conduct for responsible fisheries. An in-depth analysis of the available literature regarding bycatch mitigation in tuna fisheries with special reference to elasmobranchs was undertaken. Studies highlighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 136 publications
0
28
0
Order By: Relevance
“…Moreover, Campana, Joyce and Manning () and Musyl and Gilman () used similar survival models and prognostic variables and independently reached the same conclusion: the only significant variable to explain survival outcomes was health condition code at retrieval and tagging. However, in terms of practical and clinical significance and “Best Handling Practices” to promote survival, it is clear that eliminating severely injurious handling practices could lower mortality rates (Favaro & Côté, ; Molina & Cooke, ; Poisson, Filmalter et al., ; Poisson et al., , ; Poisson, Séret et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Campana, Joyce and Manning () and Musyl and Gilman () used similar survival models and prognostic variables and independently reached the same conclusion: the only significant variable to explain survival outcomes was health condition code at retrieval and tagging. However, in terms of practical and clinical significance and “Best Handling Practices” to promote survival, it is clear that eliminating severely injurious handling practices could lower mortality rates (Favaro & Côté, ; Molina & Cooke, ; Poisson, Filmalter et al., ; Poisson et al., , ; Poisson, Séret et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent evaluation against the IUCN Red List criteria, about one‐quarter of elasmobranch species were listed as threatened due to overfishing (Dulvy, Fowler, Musick, Cavanagh & Kyne, ) and reducing fishing mortality is a global priority to rebuild stocks (Camhi, ; Dulvy, Baum, Clarke, Compagno & Cortés, ). Due to declining populations, more species are being protected through retention bans (IATTC, ; ICCAT, , , , ; IOTC, , ; Poisson, Crespo, Ellis, Chavance & Pascal, ; WCPFC, , ) with implicit or explicit aims of reducing fishing mortality, which will result in higher discard (i.e. released after capture) rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the United States National Marine Fisheries Service (NMFS) in USA and the Department of Fisheries and Oceans (DFO) in Canada have conducted observer programs to monitor commercial fishing vessels targeting tuna, swordfish and sharks. In addition, other measures including the reduction of fishing effort targeting sharks, time/area closure in certain seasons and gear restrictions have been adopted in the North Atlantic [116,[118][119][120]. Notably, many large pelagic sharks are overfished or in overexploitation and are often removed as bycatch in longline fisheries targeting tuna and swordfish in the North Atlantic as a whole [11,54,117].…”
Section: Chondrichthyes Bycatch In the North Atlantic And Potential Smentioning
confidence: 99%
“…Recently, specific technical mitigation measures have been proposed and implemented in order to reduce bycatch mortality. Some authors suggested the use of circle hooks rather than J-hooks to increase post-release survival of large pelagic sharks in longline fisheries [71,72,120].…”
Section: Chondrichthyes Bycatch In the North Atlantic And Potential Smentioning
confidence: 99%